Alterações Morfológicas e Desempenho de Cordornas Poedeiras Tratadas com Diferentes Programas de Alimentação no Período de Repouso, da Muda Forçada - Garcia, ES [UNESP]; Mendes, AA [UNESP]; Pizzolante, CC; Veiga, Nabor [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2001)
O experimento objetivou avaliar as alterações físicas, produção de ovos e mortalidade de codornas poedeiras alimentadas por diferentes períodos com milho moído após muda forçada. Utilizou-se um delineamento inteiramente ao acaso, com três tratamentos (0, 4 e 7) dias de alimentação com milho moído e quatro repetições de 30 aves por parcela para análise do peso vivo e mortalidade e duas aves por parcela para análise das características físicas. Os resultados mostraram involução do aparelho reprodutivo até o quarto dia após muda forçada. Após sete dias, as aves alimentadas com ração de produção atingiram o peso que possuíam antes da muda forçada, e aos onze dias, as aves alimentadas com milho moído por sete dias não haviam ainda recuperado o peso de aparelho reprodutivo existente antes da muda forçada.

This research was conducted with the objective to evaluate the physical alterations, productive and mortality tracts in layer quails during the fast period and rest period when fed by different periods with corn meal and to study their effects on the production period. During the fast period, a completely randomized design with four treatments (0, 1, 2, and 3) days of fast, and three replicates of 36 birds per pen were used. In the rest period, a completely randomized design with three treatments (0, 4, and 7) days of feeding with corn meal and four replications of 30 birds per pen for live weight, egg production and mortality for analysis and two birds per pen for physical characteristics analysis were used. Results showed that there was a regression of the reproductive tract continued to the four days of the rest period. To the seven days of the rest period, the birds fed with production ration reached the weight that they had before the beginning the fast, and to the eleven days, the birds fed with corn meal during seven days had not still recovered the weight of the reproductive tract before the beginning of the fast period.
Morphological Changes and Performance of Laying Quails Under Different Feeding Schedules During the Rest Period of Forced Moulting
Keywords: codornas; muda forçada; produção de ovos; programa de alimentação; layer quails; egg production; forced molt